Feasibility Study for the Fast Periodic Pulsed Reactor with UO2 Fuel - Zhang, Liang; Jiang, Xinbiao; Zhang, Xinyi; Ma, Tengyue; Chen, Sen; Wang, Lipeng; Li, Da; Chen, Lixin (Frontiers in Energy Research, 2021)
In order to study the feasibility of the fast periodic pulsed reactor with UO2 as fuel (abbreviated as FPPRU), the core models with different load schemes are designed. Neutronic characteristics of two typical design schemes are compared, and the better design scheme is determined. The critical search method is established for analyzing the reactor dynamics. Furthermore, the theoretical estimation formulas are derived to study the factors affecting the reactor dynamics clearly and intuitively. The reactor dynamics of the fast periodic pulsed reactor with UO2 and PuO2 as fuel are compared. The thermal hydraulic characteristic of FPPRU is studied with the sub-channel model. The results show that the design scheme of the FPPRU meets the demand of neutronics and thermal hydraulics safety. Meanwhile, the pulse parameter quality of the FPPRU with UO2 as fuel is not as good as that of IBR-2 with PuO2 as fuel.